2007
DOI: 10.1536/ihj.48.485
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Properties of the Atrium After Cardioversion of Chronic Atrial Fibrillation Relation to the Plasma Brain Natriuretic Peptide Level

Abstract: SUMMARYBackground: Brain natriuretic peptide (BNP) level has been shown to increase in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Elevation of plasma NT-proBNP levels, despite the absence of obvious structural heart disease, was evident in patients with chronic AF, and no relationship was found between plasma NT-proBNP levels and intra-atrial conduction time (measured as the filtered Pdur) after cardioversion, in a previous study [27]. Evaluation of patients with persistent AF found that the baseline plasma BNP level and the magnitude of the decrease thereof after successful cardioversion, predicted AF recurrence [28].…”
Section: Relationships Of Pwd and Atrial Emd To Nt-probnp Levelsmentioning
confidence: 99%
“…Elevation of plasma NT-proBNP levels, despite the absence of obvious structural heart disease, was evident in patients with chronic AF, and no relationship was found between plasma NT-proBNP levels and intra-atrial conduction time (measured as the filtered Pdur) after cardioversion, in a previous study [27]. Evaluation of patients with persistent AF found that the baseline plasma BNP level and the magnitude of the decrease thereof after successful cardioversion, predicted AF recurrence [28].…”
Section: Relationships Of Pwd and Atrial Emd To Nt-probnp Levelsmentioning
confidence: 99%
“…1,2) It has been proven in previous studies that enhanced activity of matrix metalloproteinases (MMPs) may also be one of the mechanisms responsible for this. 3,4) It has been shown in animal studies that metalloproteinases in endocardial cells could be activated by homocysteine (Hcy).…”
mentioning
confidence: 99%
“…The precise mechanism explaining this BNP elevation has not been elucidated, but we showed previously that the BNP level was significantly higher in patients with AF than in those without AF, despite similar LVEFs. 21) LV diastolic dysfunction seems to increase secretion of BNP from the atria. 22,23) In the present study, plasma ANP and BNP levels were higher in patients with LAAT than in those without LAAT.…”
Section: Discussionmentioning
confidence: 97%